Implementing a polarisation-sensitive sensor in a plug-and-play QKD system - Pawlikowska, Estera; Życzkowski, Marek; Pakuła, Anna; Marć, Paweł (Opto-Electronics Review, 2025)
We present the results of simplified polarimetric methods for detecting disturbances on a fibre-optic link in a quantum key distribution system. The proposed methods use a polarisation coupler and a single polariser as a polarisation-sensitive detection system. The effectiveness of the disturbance detection was considered in a plug-and-play quantum key distribution system with phase encoding. This paper compares the performance of two simplified methods for determining changes in the state of polarisation in response to three types of disturbances, including touching, bending, and inserting a clip-on coupler. Also, the results of an experiment involving the entire procedure of introducing eavesdropping into a telecommunications fibre-optic cable are presented. The results of the measurements indicate the subsequent steps when attacking a fibre-optic cable. This article shows that a simplified polarisation-sensitive sensor can be implemented into a quantum key distribution system to detect disturbances and eavesdropping attempts, as well as enhance the security of the system.